Getting there from here: a literature review on vocational education and training reform implementation - Caves, Katherine [Verfasser]; Baumann, Severine [Verfasser]; Renold, Ursula [Verfasser] (My University, 2021)
"Vocational education and training (VET) reform is increasingly common, but there is more evidence on designing VET reforms than implementing them. This literature review searches the existing literature on VET reform implementation for key determinants, trends, and gaps using a determinant framework. We review 1,835 sources, coding 177 for 1,538 data points. We find that, like other implementation domains, resource- and stakeholder-related determinants are very important. For VET specifically stakeholders include employment-system actors and the relationships among actors are key. The major determinants are more like necessary than sufficient conditions, and mainly operation in conjunction with others. Europe is more represented than other continents. The findings in the literature are consistent over time, type, continent, and development status, but it is not clear if that is due to consensus or stagnation. The field is growing, however, so future research can develop theory by developing and testing hypotheses." (authors' abstract; BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; I 1 Internationale Berufsbildung; Berufsbildung; Berufsbildungspolitik; Reform; Modernisierung; Literaturanalyse